Re-imaging malaria in the Philippines: how photovoice can help to re-imagine malaria - Iskander, Dalia (Malar J, 2015)
BACKGROUND: This paper responds to a recent call for malaria to be re-imagined by: explaining why it needs to be re-imagined; offering one possible way in which this can be done; and describing some of benefits for malaria control when it is. METHODS: This study involved conducting a 15-week photovoice project with 44 predominantly ethnically Palawan school-going children in the municipality of Bataraza in the Philippines. The primary aim was to critically examine how facilitating children to take their own pictures of malaria could alter their understanding of it as well as the practices that they then engaged into prevent and treat it. RESULTS AND DISCUSSION: During the photovoice process, participants responded to the question, ‘what does malaria mean to you?’ by photographing multiple versions of malaria. Some of these versions align with biomedical conceptions and mirror common images of: its sources (e.g. mosquitoes); symptoms (e.g. fever); prevention practices (e.g. use of mosquito nets); diagnostic practices (e.g. use Rapid Diagnostic Tests) and treatment practices (e.g. use of anti-malarial drugs). However, in addition to these depictions, participants also took images of malaria that aligned with more local understanding of the body, health and well-being, which are often neglected by health practitioners. In the case of the Palawan, these versions of malaria are structured around the central tenet of balance. Participants therefore photographed themselves and members of their family and community engaging in a number of practices, which are orientated towards restoring and maintaining balance. As well being an effective means to illuminate multiple malarias and the practices that surround them, photovoice also enabled participants to learn new things and significantly, teach these things to others using their images. CONCLUSION: Photovoice is an effective method for re-imaging malaria. It allowed participants to depict and describe multiple versions of malaria and the practices that they engage in in context. Photovoice also had a potentially transformative effect. It acted as a means for participants and researchers to: visually depict everyday practices; collectively gain a deeper understanding of this doing; and then seek ways in which to make changes in line with this joint understanding.